Comparing Fetal Weight Estimates in the Third Trimester: Clinical Examination Findings, Ultrasonographic Estimation, and Actual Birth Weight - Ghaffar, Ayesha; Ashraf, Sabeen; Khan, Hafiza Alia Akbar; Yousaf, Saba; Farkhanda, Tallat; Rabbal, Amartur (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the relationship between fetal weight on clinical and ultrasonographic examinations and actual birth weight during the third trimester of pregnancy. Method: This descriptive cross-sectional study was conducted in Obs/Gynae from January 2023 to June 2023. A total of 1130 women between the ages of 18 and 40, gestational age of > 34 weeks, BMI of 18 to 25 kg/m2, single cephalic fetus and who gave consent were included. The patients with PIH, preeclampsia, eclampsia, anaemia, chronic renal disease, diabetes and conditions such as polyhydramnios, oligohydramnios, and congenital fetal anomalies were excluded from the study. The demographic information was recorded. By using Johnson’s formula, patients go through CEFW. The skilled radiologists performed an ultrasound on every female to obtain UEFW. The Shepard formula was used to calculate the FW. Following that, females were monitored till the birth of the fetus. The baby’s actual birth weight (ABW) was recorded at birth. Pearson correlation was used to determine the relationship’s correlation value between the ABW, CEFW, and UEFW. P values lower than 0.05 were regarded as significant. Results: The patients’ average age was 25.19±4.26 years. According to the gender breakdown of infants, 619 females (54.8%) and 511 males (45.2%) were born. 207 patients (18.3%) were primigravida and 923 patients (81.7%) were multiparous. The connection between CEFW and ABW was high (r=0.890; p 0.001), and UEFW and ABW were correlated with one other likewise (r=0.934; p 0.001). The following were the mean values of the various variables: Gestational age (weeks): 37.51±2.06; height (cm): 163.97±3.39; weight (kg): 76.43±6.65; BMI (kg/m^2): 28.60±2.80; SFH: 36.63±1.46; CEFW (gms) 3061.50±367.66, UEFW (gms) 3014.42±339.71 and ABW (gms) 3059.12±310.32. Conclusion: According to the findings of our investigation, both clinical estimation and ultrasound estimation produced results that were both practicable and trustworthy. Both displayed a favourable link to the real birth weight.